2010
DOI: 10.1111/j.1476-5381.2010.00982.x
|View full text |Cite
|
Sign up to set email alerts
|

Japanese encephalitis virus induces matrix metalloproteinase‐9 in rat brain astrocytes via NF‐κB signalling dependent on MAPKs and reactive oxygen species

Abstract: BACKGROUND AND PURPOSEJapanese encephalitis virus (JEV) is a member of the family Flaviviridae and JEV infection is a major cause of acute encephalopathy in children, which destroys cells in the CNS, including astrocytes and neurons. However, the detailed mechanisms underlying the inflammatory action of JEV are largely unclear. EXPERIMENTAL APPROACHThe effect of JEV on the expression of matrix metalloproteinase (MMP)-9 was determined by gelatin zymography, Western blot analysis, real-time PCR and promoter assa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
49
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 52 publications
(54 citation statements)
references
References 63 publications
5
49
0
Order By: Relevance
“…Recently, Tung et al [64] demonstrated that JEV-induced MMP-9 expression occurs at transcriptional and translational levels, which supports our data. They also demonstrated that JEV stimulated MMP-9 expression that was mediated through the generation of ROS and activation of NADPH oxidase, p42/p44 MAPK, p38 MAPK, JNK1/2, and NF-ĸB in RBA-1 cells.…”
Section: Discussionsupporting
confidence: 82%
“…Recently, Tung et al [64] demonstrated that JEV-induced MMP-9 expression occurs at transcriptional and translational levels, which supports our data. They also demonstrated that JEV stimulated MMP-9 expression that was mediated through the generation of ROS and activation of NADPH oxidase, p42/p44 MAPK, p38 MAPK, JNK1/2, and NF-ĸB in RBA-1 cells.…”
Section: Discussionsupporting
confidence: 82%
“…A previous study determined that an increased level of ROS could induce the upregulation of MMPs by MAPK/NF-kB signaling. 22 To investigate whether NF-kB upstream modulators participate in the inhibitory functions of GbE-mitigated oxLDL-caused activation of MMPs, endothelial cells were pretreated with pharmacologic inhibitors of ROS (DPI), Ca þþ , (1,2-bis(o-aminophenoxy) ethane-N,N,N 0 ,N 0 -tetraacetic acid [BAPTA]), PKC-a/b (Gö6976), and ERK (PD98059). As demonstrated in Fig 6, the expression of oxLDL-promoted ERK phosphorylation and NF-kB activation, which is downstream of ERK phosphorylation, was conspicuously restrained in cells pretreated with GbE, DPI, BAPTA, Gö6976, and PD98059.…”
Section: Resultsmentioning
confidence: 99%
“…No apparent induction of metalloproteinase activity was detected in endothelial cells infected with JEV and exposed to JEV-conditioned medium. An elevated expression of metalloproteinase was demonstrated in rat astrocytes in response to JEV infection (42). That is, despite the crucial role of metalloproteinases in endothelial barrier integrity, their inductive expression varies and depends on cell types, stress, and microenviroments.…”
Section: Discussionmentioning
confidence: 98%